Zyxin stabilizes RIG-I and MAVS interactions and promotes type I interferon response - Takahisa Kouwaki (Nature Portfolio, 2017)
Abstract RIG-I and MDA5 are cytoplasmic viral RNA sensors that belong to the RIG-I-like receptors (RLRs), which induce antiviral innate immune responses, including the production of type I interferon and other pro-inflammatory cytokines. After recognition of viral RNA, the N-terminal caspase activation and recruitment domains (CARDs) of RIG-I and MDA5 bind to a CARD in the MAVS adaptor molecule, resulting in MAVS oligomerization and downstream signaling. To reveal the molecular mechanism of MAVS-dependent signaling, we performed a yeast two-hybrid screening and identified zyxin as a protein that binds to MAVS. Zyxin co-immunoprecipitated with MAVS in human cells. A proximity ligation assay showed that zyxin and MAVS partly co-localized on mitochondria. Ectopic expression of zyxin augmented MAVS-mediated IFN-β promoter activation, and knockdown of zyxin (ZYX) attenuated the IFN-β promoter activation. Moreover, ZYX knockdown reduced the expression of type I IFN and an interferon-inducible gene after stimulation with polyI:C or influenza A virus RNA. Interestingly, physical interactions between RLRs and MAVS were abrogated by ZYX knockdown. These observations indicate that zyxin serves as a scaffold for the interactions between RLRs and MAVS.